Sustainability of Local Media in the Era of Disruption: A Case Study of AyoBandung.com - Bani, Bibo; Aristi, Nindi; Mirawati, Ira (UI Scholars Hub, 2026)
This study examines the sustainability strategy of local media in responding to the challenges of digital disruption in the media industry. The case selected for the research is AyoBandung.com, local digital news portal under PT Ayo Media Network. Local media are structurally vulnerable to platform dominance, forcing them to balance journalistic integrity with economic adaptation. This research employs a qualitative case study approach, with data collected through in-depth interviews with internal stakeholders, including editorial and business management teams. The findings reveal a clear structural and functional separation between the AyoBandung and creative agency, with distinct workflows, content types, and distribution platforms. While the editorial team remains focused on public- interest journalism, the creative agency contributes to the company’s commercial sustainability by producing client-based content. The study demonstrates that synergy between these two distinct units serves as a viable sustainability strategy for local media outlets navigating the continuously evolving digital media landscape. The study contributes theoretically by extending discussions on organizational ambidexterity in local journalism, demonstrating how editorial exploitation and commercial exploration can coexist without undermining credibility. Practically, the findings offer a replicable model for local media seeking financial resilience: diversification through creative services, combined with clear ethical boundaries, can support sustainability while preserving journalistic trust.